Development and application of paleolimnological analyses to disentangle the roles of natural processes and anthropogenic activities on contaminant deposition and hydrological conditions across a northern delta - Kay, Mitchell (University of Waterloo, 2022)
Freshwater ecosystems across northern Canada provide important habitat for wildlife and have long supported the traditional lifestyles of Indigenous communities. Multiple potential stressors threaten the security of water supply to northern landscapes, which fosters need for information spanning broad spatial and temporal scales to inform adaptive and mitigative strategies. At the Peace-Athabasca Delta (PAD; northern Alberta), the world's largest boreal freshwater delta, existing data records have been too short and too sparse to resolve many concerns over the roles of major energy projects (hydroelectric regulation of river flow, oil sands development) and climate change on decline of flood frequency and magnitude and drawdown of shallow aquatic basins, and on supply of substances of concern. Intensive paleolimnological research during the past two decades at the PAD has evaluated past changes in contaminant deposition and hydroecological conditions to discern effects attributable to oil sands development along the Lower Athabasca River and to regulation of Peace River flow by the W.A.C. Bennett Dam. This thesis builds substantially on these previous studies to address knowledge gaps by applying conventional paleolimnological methods at new locations to improve understanding of temporal changes in contaminant deposition and hydrological change and developing an innovative paleolimnological approach for discerning variation in sediment sources over space and time to lakes within the PAD. Concerns of pollution in the PAD stem from potential for dispersal of contaminants released by bitumen mining and processing activities within the Alberta Oil Sands Region (AOSR), which straddle the Lower Athabasca River. Unfortunately, systematic monitoring began thirty years after onset of oil sands development and sampling locations have changed over time, which has hampered the ability to accurately track temporal trends or attribute sources of pollution at the AOSR and downstream locations. Previous paleolimnological ...